Simbolisasi Punokawan dalam Iklan - Meirina Lani Anggapuspa (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2014)
Advertising in its function as a medium conveys the message, of course, have a variety of ways to convey the message properly to the audience, one of which is through symbolization Punokawan figure. Punokawan are officials in the puppet character that is not just qualified, but can also directing, comforting, encouraging, and motivating. Use of this Punokawan figures, aims to bring back the ethos and nature of mutual assistance (bebarengan mrantasi gawe) that characterize the people of Yogyakarta. In addition, these symbolization Punokawan also able to arouse the human willingness to back attitude with a calm and humble, without the prestige and show off everyday to fulfill its obligations, and seek not to impose its own sake, for the sake of harmony in the society Playing the disaster and post-disaster reconstruction.